Effects of organizational structure on social value: mediating role of financial performance / Nur Aima Shafie ... [et al.] - Shafie, Nur Aima; Mohd Sanusi, Zuraidah; Johari, Razana Juhaida; Utami, Wiwik; Ghazali, Aziatul Waznah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Social enterprise (SE) is a hybrid organisation, which combine two different goals in their mission and vision. In an attempt to sustain their operation, social enterprise must ensure that both mission (social and financial) is equally balanced and achievable. The existence of SE is to fill the gap leave behind by traditional profit organisation, non-profit organisations (NPOs) and the government. The aim is to positively impact the social, cultural and environmental issues through their unique business model. Their uniqueness, while can benefit the community and society as a whole is prone to fraud and misuse of funds which would eventually affect the survival of SE. The issues are originated from weak governance particularly the structure of their organisations. Hence, this study is aims to examine the relationship between the organisational structure, financial performance and social value of SE in Malaysia. On the other hand, the study also aim to examine the mediating role of financial performance on the relationship between organisational structure and social value. Organisational structure is vital as carefully selected, well designed and well managed organisational structure will improve the impact of social enterprise on the society. This study is based on the 134 data obtained from the SE in Malaysia and registered as Company Limited by Guarantee (CLBG). The study found that, organisational structure and financial performance significantly influence the social value of SE. Furthermore, it was also found that financial performance indeed mediate the relationship between organisational structure and social value. It is hoped that the study can contribute to the improvement of performance of SE in Malaysia and as well as encourage the development of research in the area of SE.